A Robust H∞ Control Approach for Blood Glucose Regulation in Type-1 Diabetes. Issue 15 (2021) - Cassany, L.; Gucik-Derigny, D.; Cieslak, J.; Henry, D.; Franco, R.; de Loza, A. Ferreira; Ríos, H.; Olçomendy, L.; Pirog, A.; Bornat, Y.; Renaud, S.; Catargi, B.
Abstract: The paper addresses the design of a H∞ closed-loop dedicated to Blood Glucose (BG) regulation for patients affected by Type-1 Diabetes Mellitus (T1DM). The closed-loop setup is standard, i.e. the H∞ feedback controller uses the information provided by a subcutaneous sensor to drive an insulin pump but as opposed to current existing solutions, it is proposed to assess the capabilities of a H∞ controller to be designed in a patient-independent way. For that purpose, the design is performed on a family of linear models in order to tackle the variability of a cohort of T1DM patients. Worst-case performance and robust margins are next computed with the help of the H∞ /µ-analysis theory. The solution is finally assessed on the adult cohort of the high-fidelity UVA/Padova benchmark (v3.2), accepted by the US Food and Drug Administration (FDA) as a substitute for pre-clinical testing of control strategies.